Biofeedback as an intervention for persistent post-concussive symptoms: A randomized feasibility trial. (November 2021) - Bonn, Marquise M; Alvarez, Liliana; Graham, Laura; Thompson, James W; Dickey, James P
Background: Case reports indicate that low-resolution electromagnetic tomography neurofeedback and heart rate variability biofeedback may improve physiological functioning in individuals with persistent post-concussive symptoms. However, it is unclear whether larger-scale studies are feasible. Purpose: To evaluate the feasibility of a combined low-resolution electromagnetic tomography neurofeedback and heart rate variability biofeedback intervention for individuals with persistent post-concussive symptoms. Methods: Individuals with persistent post-concussive symptoms were randomized into intervention and control groups, and their baseline and post-test assessments were compared to a healthy control group. Outcomes included self-report questionnaires, resting electroencephalograph and electrocardiograph recordings, and a driving simulation task. Participants in the intervention group completed three 20 min low-resolution electromagnetic tomography neurofeedback sessions per week and at-home heart rate variability biofeedback training every morning and night for 8 weeks. Feasibility was evaluated according to recruitment capability and sample characteristics, data collection procedures, suitability of the intervention and study procedures, management and implementation of the study intervention, and preliminary participant responses to the intervention. Results: Thirty-three individuals were recruited and 24 completed this study (seven intervention participants, nine persistent post-concussive symptoms control participants, and eight healthy control participants). One-quarter of participants (four intervention participants and three persistent post-concussive symptoms control participants) experienced simulator sickness during the driving simulator task and had to withdraw from the study. Intervention participants had an 88% and 86% compliance rate for the low-resolution electromagnetic tomography neurofeedback and heart rate variability biofeedback sessions, respectively. Low-resolution electromagnetic tomography neurofeedback sessions took approximately 1 h to complete per participant. Preliminary analysis indicated that the intervention reduced electroencephalograph z -score deviation with a very large effect size ( d  = 1.36) compared to the other study groups. Conclusions: Pilot studies evaluating the efficacy of low-resolution electromagnetic tomography neurofeedback and heart rate variability biofeedback should be performed to confirm these preliminary findings. However, the protocol should be modified to reduce participant fatigue and withdrawal. This trial was registered with Clinicialtrials.gov (NCT03338036;https://clinicaltrials.gov/ct2/show/NCT03338036?term=03338036&draw=2&rank=1 ).